Does Economic Efficiency matters? Evidence from Microfinance Sector of Pakistan - Maeenuddin,; Hamid, Shaari Abd; Nassir, Annuar MD; Ghayasuddin, (The journal of contemporary issues in business and government, 2021)
According to the World Bank, the microfinance sector all over the globe, especially in developing countries has increased significantly and received tremendous attention for the last ten years.However, on the other hand, the amount of poor people is not decreasing. To understand this phenomenon, this study focuses to explore the economic efficiency of microfinance providers and to investigate the various factors or determinants that have an impact on the economic efficiency of microfinance providers. Economic efficiency gets its ground on the concept of the resources’ scarcity. Economic efficiency means creating maximum outputs from minimum inputs and avoiding wasteon the resources. Data Envelopment Analysis (DEA) approach was used to calculate the economic efficiency level, with the inputs arethe staff size and the operational expenses. As for the outputs, they are the borrower numbers, gross loan portfolio, and operational self-sufficiency ratio. Regression analysis was used to examine the impacts of different factors on the microfinance providers’ economic efficiency. The result shows that the factors which affect the economic efficiency of microfinance providers arethe empowerment, organizational structure, aggressive marketing programs, optimum balance of available financial resources, profit-oriented programs, growth outreach, commercialization, competition, cultural dimensions, Interest rates, growth addiction, stability or short term profitability focus, loan repayment focus, minimum follow-up programs, minimum awareness, loan misuse, fear of defaults, and lack of technical support.These factors have to be considered for future studies.